Highly Lithiophilic Three-Dimension Framework of Vertical CuO Nanorod Arrays Decorated Carbon Cloth for Dendrite-Free Li Metal Anode - Kang Wang; Derong Liu; Ping Yu; Hongyu Gong; Xiaoping Jiang; Meng Gao; Dongwei Li (Batteries, 2023)
An Li metal anode has been proposed as a promising candidate for high energy density electrode material. However, the direct use of Li metal can lead to uncontrollable dendrite growth and massive volume expansion, which generates severe safety hazards and hinders practical application. Herein, we developed a novel Li anode by thermal infusion into three-dimensional (3D) carbon cloth (CC) modified with lithiophilic CuO nanorod arrays (denoted as Li@CuO−CC). The 3D CC offers sufficient space for Li storage and adequate electrolyte/electrode contact for fast charge transfer. The uniformly distributed CuO nanorod arrays can improve the lithiophilicity of CC and redistribute the Li-ion flux on the substrate, leading to uniform Li stripping/plating behavior. As a result, the Li@CuO−CC electrode exhibits a dendrite-free feature and superior cycling performance over 1000 h with low overpotential (12 mV) at a current density of 1 mA cm−2 in the symmetrical cell without significant fluctuations. When coupled with an LiFePO4 cathode, the full cell displays high specific capacity (133.8 mAh g−1 at 1 C), outstanding rate performance, and cycle stability (78.7% capacity retention after 600 cycles at 1 C). This work opens a new approach for the development of construction of an advanced anode for Li metal batteries.